Sustainable City Planning and Development: Transport and Land Use (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Fostering sustainable city planning and development requires a holistic understanding of the complex interactions between transport and land use. In other words, to promote sustainable city planning and development, systematic and thorough assessments and a deeper comprehension of the interactions between transport and land use are needed, especially for today’s cities.